Analisys and Implementation Cloud-based Biometricauthentication in Mobile Platform - agostinho marques ximenes; Sritrusta Sukaridhoto; Amang Sudarsono; Hasan Basri (Universitas Trunojoyo Madura, 2019)
Based on the Indonesian Central of Statistics the level of poverty people in September 2018 was 25.95 million, based on data, the government allocation care fund the reduce poverty people, the fund are given through the bank. However, banks cannot allocation funds because the cost for build infrastructure is expensive, such as making an ATM. about that, the banks need to find a new solution to allocation care fund to the poverty people, Mobile Platform Biometric Cloud Authentication is one solution. In this study, the experimentationn of the biometric face recognized( face data enrypt and decript by algoritma AES 256 bit) to secure online payment mobile application based on the QR Code scan and face recognition[8,10]. The concentration of this study lies in the experimentationn of biometric face recognize and QR Code scan on biometric payment based face recognition and QR Code scan mobile applications that play a role in data communication security. The test results on this mobile application show that scanning a QR Code and biometric face recognize can be implemented at an online merchant transaction with an accuracy of 95% and takes 53, 21 seconds in transactions. Keyword: biometric, cloud server, Cryptography, QR Code.